EFFECTIVENESS OF PHYSICS-BASED LEARNING LESSON STUDY WITH MULTIREPRESENTATION TO COACH STUDENT PROCESS SKILLS ON BASIC PHYSICS COURSE I - Syahril Syahril; Muhammad Sahal; Fakhruddin Fakhruddin (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
This study aims to determine the effectiveness of of physics-based learning lesson study with multirepresentation on Basic Physics course I. The subjects of the study are the first level students as much as 42 people divided into 2 classes, namely experimental and control class. The data completion instrument is a skill test consisting of 5 items about the essay. Data analysis is descriptive analysis to see the picture of result learn student process skill by using absorption criterion, learning efficiency, and mastery learning at presenter and postest. The data analysis showed that the average absorption rate of the class was 9.28% with the less favorable category in pretest experimental class at posttest 17.78% less good and 9,30% with less good category for control class at pretest and 17,18% With less good category, while the quality of less effective learning with 0% percentage in the experimental class and 0% for the control class in the category of less effective, student's 0% complete student completeness and incomplete start in pretest experimental class and 4.76% unfinished postest, and 0% at pretest with unfinished category, 14.29% also incomplete for postest control class, and 0% completeness of subject matter and unfinished acceptance in experiment class and 0% unfinished in control class Pretest and postest Thus, it can be concluded by using the programming language used for learning English on Basic Physics course I on the mater I collision and momentum.